The efforts of health-care professionals in preparing their families for situations requiring first aid - Sahar Khalid; Anas Khan; Adel Altamimi; Osama Samarkandi (Wolters Kluwer Medknow Publications, 2019)
Objective: The aim of the study is to assess the efforts of health-care professionals (HCPs) in preparing their families for situations requiring first aid (FA). We hypothesized that if HCPs are genuinely committed and convinced of the importance of FA, then they will be more likely to share this belief and knowledge and act in a way that will positively affect their family members, social surroundings, and consequently, the community. Materials and Methods: This was a cross-sectional survey conducted in Saudi Arabia from December 2017 to January 2018. The calculated sample size was 384. An online form was uploaded on Twitter to allow any willing HCP to participate. HCPs who responded to the survey were included in the study. Exclusion criteria were being a non-HCP or a HCP from outside of Saudi Arabia. Results: Among 655 participants, 352 (53.7%) taught family members at least one of the FA maneuvers in a detailed manner, including cardiopulmonary resuscitation, seizure or choking management, and control of excessive bleeding. Participants were more inclined to have a positive attitude toward teaching FA if their family members had witnessed a situation, in which a FA intervention was required (250 [38.2%]; P < 0.001). Majority (479, 73.1%) of the participants knew that 70% of out-of-hospital cardiac arrests happen at homes and were significantly more likely to have a positive attitude (P < 0.001). Conclusion: The majority of HCPs have made and contributed to preparing their families for situations requiring FA.